Explanation of the Structural–Interpretive Model of the Direct Effects of Sports on the Macroeconomy of Iranian Metropolises - Alizadeh, Reza; Kharazian, Shahriar; Hatef, Hakimeh; Hosseinzadeh Gonabadi, Ali (Management Strategies and Engineering Sciences, 2026)
The aim of this study was to explain a structural–interpretive model of the direct effects of sports on the macroeconomy of metropolises in Iran. This research was applied in purpose, qualitative in terms of data type, exploratory in data analysis method, present-oriented in time perspective, and field-based in data collection. The statistical population consisted of faculty members and individuals managing public sectors related to economic development, such as municipal managers, city council members, and directors of the Departments of Sport and Youth in several major provinces. The theoretical (purposive) sampling method was applied until theoretical saturation was reached, which was ultimately achieved after nine interviews. In the structural–interpretive modeling stage, a Delphi panel was formed with five experts specializing in the field of sports economics, and the components were subsequently scored. In total, 34 open codes were identified and categorized into six axial codes and one selective code representing the direct effects of sports on metropolises. Structural–interpretive modeling was performed using the MICMAC software, and the results showed that sports services and sports competitions were the most influential components, while sportswear production was the least influential factor among other components affecting the macroeconomy of metropolises in Iran. Considering the direct impact of sports on the urban economy of large cities, it appears essential that policymakers and city officials pay increased attention to the development of sports in major urban areas.